Reproductive and pregnancy outcomes of fertility-sparing treatments for early-stage endometrial cancer or atypical hyperplasia: A systematic review and meta-analysis. (June 2022) - De Rocco, Silvia; Buca, Danilo; Oronzii, Ludovica; Petrillo, Marco; Fanfani, Francesco; Nappi, Luigi; Liberati, Marco; D'Antonio, Francesco; Scambia, Giovanni; Leombroni, Martina; Dessole, Margherita; Lucidi, Alessandro
Abstract: Objective: To report the pregnancy outcomes of women with prior endometrial cancer and endometrial hyperplasia managed with fertility-sparing treatments. Methods: Medline and Embase databases were searched. Inclusion criteria were studies reporting the pregnancy outcomes of women who had undergone fertility-sparing treatments for endometrial hyperplasia or early endometrioid endometrial cancer. Outcomes explored were pregnancy, miscarriage and livebirth rates according to the type of progestin treatment used. Subgroup analyses according to the type of diagnostic follow-up were also performed. Meta-analyses of proportions using a random effects model were used to combine data. Results: Twenty-nine studies (1036 women) were included, and 82.8% [95% confidence interval (CI) 72.3–91.2] of women achieved complete remission. Pregnancy rates were 56.3% (95% CI 41.6–70.5) with megestrol (MA) or medroxyprogesterone acetate (MPA), 63.1% (95% CI 37.0–85.6) with levonorgestrel-releasing intrauterine device (LNG-IUD), 57.9% (95% CI 37.7–76.8) with MA or MPA and metformin, 59.8% (95% CI 48.3–70.7) with MPA and LNG-IUD, 15.4% (95% CI 4.3–42.2) with gonadotropin-releasing hormone analogue (GnRHa) combined with LNG-IUD or letrozole, and 40.7% (95% CI 24.5–59.3) with LNG-IUD and GnRHa. Miscarriage rates were 17.4% (95% CI 12.2–23.4), 14.3% (95% CI 6.4–24.7), 57.9% (95% CI 37.7–76.8), 26.9% (95% CI 14.6–39.3), 100% (95% CI 34.0–100) and 18.2% (95% CI 5.1–47.7), respectively, and livebirth rates were 68.8% (95% CI 56.0–80.3), 80.8% (95% CI 69.5–90.0), 69.9% (95% CI 56.1–82.0), 25.97 (95% CI 14.6–39.3), 0% (95% CI 0–66.0) and 81.8% (95% CI 52.3–94.8), respectively. Finally, stratifying the analysis considering the endometrial sampling method alone, the pregnancy rate was 68.6% (95% CI 51.2–83.6; 10 studies, I 2 = 83.5%) in women who underwent hysteroscopy and 60.5% (95% CI 53.4–67.5; 13 studies, I 2 = 39.8%) in women managed with dilatation and curettage biopsy; the miscarriage and livebirth rates were 13.2% (95% CI 8.0–19.5; I 2 = 0%) and 81.2% (95% CI 67.4–91.8; I 2 = 67.3%), respectively, for hysteroscopy, and 25.2% (95% CI 17.8–33.3; I 2 = 15.5%) and 67.5% (95% CI 58.8–75.5; I 2 = 0%), respectively, for dilatation and curettage biopsy. Conclusion: Fertility-sparing treatment in women with endometrial cancer or hyperplasia is associated with an overall good response to therapy, good chance of achieving pregnancy and a good livebirth rate. Diagnostic follow-up with hysteroscopy was associated with a higher pregnancy rate, although this requires confirmation in adequately powered randomized trials.